Limiting worker exposure to highly pathogenic avian influenza a (H5N1): a repeat survey at a rendering plant processing infected poultry carcasses in the UK - Afza Musarrat; Edeghere Obaghe; Coetzee Nicol; Duggal Harsh V (BMC Public Health, 2011)
Abstract Background Current occupational and public health guidance does not distinguish between rendering plant workers and cullers/poultry workers in terms of infection risk in their respective roles during highly pathogenic avian influenza poultry outbreaks. We describe an operational approach to human health risk assessment decision making at a large rendering plant processing poultry carcasses stemming from two separate highly pathogenic avian influenza A (H5N1) outbreaks in England during 2007. Methods During the first incident a uniform approach assigned equal exposure risk to all rendering workers in or near the production line. A task based exposure assessment approach was adopted during the second incident based on a hierarchy of occupational activities and potential for infection exposure. Workers assessed as being at risk of infection were offered personal protective equipment; pre-exposure antiviral prophylaxis; seasonal influenza immunisation; hygiene advice; and health monitoring. A repeat survey design was employed to compare the two risk assessment approaches, with allocation of antiviral prophylaxis as the main outcome variable. Results Task based exposure assessment during the second incident reduced the number of workers assessed at risk of infection from 72 to 55 (24% reduction) when compared to the first incident. No cases of influenza like illness were reported in workers during both incidents. Conclusions Task based exposure assessment informs a proportionate public health response in rendering plant workers during highly pathogenic avian influenza H5N1 outbreaks, and reduces reliance on extensive antiviral prophylaxis.